Minimizing wind drift of an arrow - Park, J. L. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2012)
The selection and performance of different arrows in a wind can be a significant differentiator between competitors in outdoor archery competitions. Lateral displacement due to wind (wind drift) has two components: the first due to the arrow aligning itself with the resultant airflow, and the second due to the lateral component of the arrow`s aerodynamic drag. In this paper those components are calculated and compared with the measured wind drift in a large wind tunnel and with the standard deviation of the group size of different arrows shot outdoors in a wind. The wind drift of arrows can be compared by considering their diameter and mass. This is used to select the optimum arrow for outdoor target archery, together with optimization of the various arrow components to minimize the wind drift of a particular arrow.